Rappresentazione insolita dei grandi fondatori della città di Roma nella Genealogia deorum gentilium di Giovanni Boccaccio - Babics, Zsófia (Verbum – Analecta Neolatina, 2011)
This paper has a twofold purpose. On the one hand, its objective is to explore two chapters concerned with Aeneas and Romulus in Boccaccio's Genealogy, more closely, to address the issue of the two heroes' death. The author ends their lives in a surprisingly similar and undeserved way, to which there is no reference in other sources. On the other hand, examining those matters, the paper wishes to point out Boccaccio’s unusual humanistic approach to the subject of his work, i.e., to heathen mythology or to the sources he exploited. In the majority of cases he prefers the latter and at times Christian authors' opinion to those of the antique writers despite the fact that he is aware of a conciderable amount of ancient sources and attempts to use each of them in his works.